1973
DOI: 10.1007/bf01906580
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen über die Flimmerschwelle des isolierten Meerschweinchen-Herzens für Gleichstrom und sinusförmigen Wechselstrom

Abstract: In isolated perfused guinea-pig hearts the threshold for ventricular fibrillation was determined applying DC or sinusoidal 50-cycle AC pulses during the vulnerable period. The results were compared with the threshold for single responses during diastole.Using rectangular pulses from 0.5 to 40 msec the threshold for fibrillation as well as for single responses exhibited a nearly linear relationship between strength and duration of impulses when plotted in a log-log-scale. As compared with the threshold for sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

1980
1980
2009
2009

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
6
0
2
Order By: Relevance
“…Moreover, in the isolated heart perfusion continues during fibrillation, whereas in the intact animal the coronary circulation is strongly reduced by the arrhythmias, rendering frequent measurements of the fibrillation threshold impossible. Although in the guinea pig heart fibrillation is usually transient, the basic mechanism of its induction and development is not different from that found for the hearts of larger animals (2,11,16,25).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, in the isolated heart perfusion continues during fibrillation, whereas in the intact animal the coronary circulation is strongly reduced by the arrhythmias, rendering frequent measurements of the fibrillation threshold impossible. Although in the guinea pig heart fibrillation is usually transient, the basic mechanism of its induction and development is not different from that found for the hearts of larger animals (2,11,16,25).…”
Section: Discussionmentioning
confidence: 97%
“…As compared with the hearts of larger animals (sheep, dogs and pigs), the guinea pig heart tends to defibrillate spontaneously (16,25). Hence possible injury of the preparation due to electrical defibrillation is avoided.…”
Section: Discussionmentioning
confidence: 97%
“…I n p r e c e d i n g s t u d i e s a c o n t i n u o u s d e c l i n e of t h e t h r e s h o l d for fibrillat i o n w a s f o u n d w i t h i m p u l s e d u r a t i o n s of u p to 40 m s (17). T h i s l e d us to e x a m i n e w h e t h e r t h e f i b r i l l a t o r y e f f i c a c y of t h e D C is f u r t h e r i n c r e a s e d if t h e r a n g e of i m p u l s e d u r a t i o n s is e x t e n d e d u p to a b o u t 100 ms,…”
Section: F I B R I L L a T I O N T H R E S H O L D F O R D C P U L S mentioning
confidence: 98%
“…The threshold for fibrillation was determined by Younossi et al (17) in isolated guinea pig hearts using DC pulses between 0.5 and 40 ms. These studies revealed a nearly hyperbolic function comprising the range of impulse strengths between about 15 and i00 mA.…”
Section: Introductionmentioning
confidence: 99%
“…von *) Deutsche Forschungsgemeinschaf t Gu 173/2 -1979. Stromimpulsserien) [2,3, 5,6,7,9,10,11,12,13,14,16,17,18]. Die biologische Bedeutung der angegebenen Stimulationsmethoden und die Übertragbarkeit der hiermit erhaltenen Ergebnisse auf Pathogenese und Therapie spontaner Arrhythmien sind zur Zeit Gegenstand klinischer und experimenteller Forschung.…”
Section: Introductionunclassified